On the influence of drained cyclic preloadings on the cyclic behaviour of Zbraslav sand. Issue 165 (February 2023) - Duque, J.; Roháč, J.; Mašín, D.
Abstract: This article experimentally evaluates the influence of directional drained cyclic preloadings on the subsequent undrained monotonic and cyclic response of Zbraslav sand. The cyclic tests were performed on dense samples and under triaxial conditions. The experiments considered several different preloading directions, magnitude of the maximum deviatoric stress reached during the drained preloading stage and deviatoric stress amplitudes during the undrained shearing stage. The experimental results suggested that the rate of strains and pore water pressure accumulation, and therefore, the number of cycles to reach initial liquefaction or failure conditions are remarkably affected by the direction of the drained preloading history. In addition, the preloading direction plays a major role on the contractive/dilative response during the subsequent undrained monotonic loading. In particular, directional drained cyclic preloadings toward positive deviatoric stresses at constant mean effective stress and isotropic compression led to more dilative responses. Contrary, preloadings toward negative deviatoric stresses at constant mean effective stress led to more contractive responses. The results suggest that these major variations cannot be associated to the rather small changes in the relative density of the samples but likely due to fabric changes and induced anisotropy caused by the drained preloading history. Highlights: Drained cyclic preloadings improve the liquefaction resistance of sands. The shear stiffness strongly depends on the stress history. Drained cyclic preloadings alter the dilatancy-contractancy characteristics of sands. Preloadings modify the accumulation rates of sands under undrained cyclic loading.